86 The use of simulated patients, relatives and healthcare professionals to enhance communication skills for challenging situations within multidisciplinary healthcare teams. (17th November 2016) - Amaradasa, N; White, L; Hamilton, C; Clarkson, G; Thomas, R
Abstract : Ten communication sessions were delivered. Scenarios were created following conversations with real patients and staff. Multidisciplinary facilitation, including a senior nurse, communication specialist, foundation programme director, simulation fellows and simulated patients set up and managed the sessions. Patient presence was also available during these sessions. Four scenarios were used; comforting a patient following unwelcome news, discussion with a relative regarding treatment for a patient lacking capacity; communicating with a colleague after disclosure of domestic abuse and challenging unprofessional behaviour. Participants rotated in multi-disciplinary groups of four ensuring that they were exposed to all scenarios and facilitators. Within these small groups, participants would take turns to engage with the actor and observe their colleagues doing likewise, encouraging all to interact during the debrief. Facilitator and actor also provided feedback. The richness of multidisciplinary feedback (doctors feeding back to nurses and vice versa) was a factor new to all participants and regarded positively. Written feedback was obtained. 74 participated; 47 doctors and 26 nurses. Feedback demonstrated this model provided a valuable learning opportunity enjoyed by the multi-disciplinary groups involved. The sessions reinforced the importance of good multi-disciplinary communication as a core value within healthcare professional codes of conduct as well as promoting a culture of compassionate care for the future.